2020
DOI: 10.3390/ani10101800
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selected Factors on the Content of Fat-Soluble Vitamins and Macro-Elements in Raw Milk from Holstein-Friesian and Simmental Cows and Acid Curd Cheese (Tvarog)

Abstract: The study was conducted to determine the content and retention of selected fat-soluble vitamins and minerals in curd cheese–tvarog made by a traditional method, taking into account the effect of the quality of the raw milk and the type of starter cultures used. The raw milk used to make the tvarog was obtained in various conditions, i.e., with and without the use of pasture forage (in a traditional and an intensive system), in two production seasons (spring/summer and autumn/winter), from two breeds raised in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…However, for animals from the group with high K tox , a more pronounced deviation in the content of chemical elements in hair from the recommended physiological range was observed compared to animals from the group with low K tox . Nevertheless, such discrepancies in the content of individual elements in the hair of cows with the recommended physiological standard were probably due to more differences in the geographical zones of animal habitation, the level of metabolic processes, age, and the genotype of animals [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…However, for animals from the group with high K tox , a more pronounced deviation in the content of chemical elements in hair from the recommended physiological range was observed compared to animals from the group with low K tox . Nevertheless, such discrepancies in the content of individual elements in the hair of cows with the recommended physiological standard were probably due to more differences in the geographical zones of animal habitation, the level of metabolic processes, age, and the genotype of animals [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Cow milk and its products are considered a valuable source of vitamins in the human diet, such as retinol (vitamin A), vitamin D 3 (cholecalciferol), tocopherol (vitamin E), vitamin K 2 (menaquinone), and β-carotene (provitamin A) [2,4,5,[147][148][149][150]. Vitamins are compounds with high biological activity that are essential for the growth and proper functioning of the body.…”
Section: Vitaminsmentioning
confidence: 99%
“…Unfortunately, the literature lacks comprehensive studies assessing mineral content in dairy products, particularly organic ones. Król et al [147] found that the content of minerals in tvarog (traditional Polish acid curd cheese) did not depend on their content in the raw milk. According to Lucas et al [177] and Manuelian et al [178], differences in the mineral composition of cheese result from the degree of acidification of the raw milk, as well as from technological factors such as heating or salting.…”
Section: Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk fat is important during the absorption of A, D, E, and K vitamins. Vitamins soluble in milk fat are very significant because they have antioxidant properties, thus also acting against viruses and bacteria (Król et al, 2020). Carbohydrates can be considered as another milk component.…”
Section: Literature Reviewmentioning
confidence: 99%